(Re)Construction of Teachers’ Value Attitudes During the Retraining Studies: The Context of Inclusive Education - Karvelienė, Regina; Rūdytė, Kristina (Social Welfare: Interdisciplinary Approach, 2026)
The paper reveals how teachers’ value attitudes change during their retraining studies by employing qualitative research methods. The (re-)construction of teachers’ value attitudes during their study period most clearly revealed itself in two major directions. The first one is related to the concept of inclusion and is treated as one of the key value-based philosophies and educational strategies of contemporary education. The second direction is associated with reflection on the teacher’s professional identity field encompassing a new perception of the self as a teacher and an individual. Moreover, the re-identification of the professional role is emphasised too. Reconstruction of teachers’ value attitudes may be positioned as a core part of the retraining studies. The findings of the qualitative study prove that teachers (re-)construct value attitudes that are relevant for the professional field when they have a possibility to reflect on their pedagogical performance, attitudes, professional skills and personal characteristics in the context of the study process and content. Reflection becomes a significant tool allowing integration of the previously obtained and newly acquired experiences. It also provides preconditions for making the process of value-based transformation visible. This means that the change of value attitudes is inseparable from reflection which, in the context of the present study, can be identified as a catalyst of the value-based transformation necessary for the (self-)formation of the professional identity.